Measurement of Marketing Data Attributes - Kupec, Václav; Kretter, Anton (Communication Today, 2025)
Marketing data are important part of the empirical marketing. That is the reason why we need to measure and analyze these data precisely. The results of the traditional information chain (data – information – knowledge) can be used as source materials for marketing management. The aim of this study is to analyze selected marketing data attributes and to propose possible approach to their measurement. The methodology of this study is to analyze the recent theories as well as the observation and modelling of behaviour of the selected marketing data such as opportuneness, accuracy and value. Among the findings of this article we can include the data opportuneness which prefers actual information, and also the accuracy which is derived from factors that create and transmit the data. We cannot forget the value of the data which takes into account mainly the time phase and the final user in comparison with the price measurements. This study also finds the possibilities of further processing of this topic mainly in the relation to the data persistence. In conclusion, we would like to state that the analyzed and measured marketing data are useful source materials for the marketing strategy of users or marketing management. JEL classification: M31.